Are Multiple Mitochondrial Related Signalling Pathways Involved in Carotid Body Oxygen Sensing? - Holmes, Andrew P.; Swiderska, Agnieszka; Nathanael, Demitris; Aldossary, Hayyaf S.; Ray, Clare J.; Coney, Andrew M.; Kumar, Prem (Frontiers in Physiology, 2022)
It is generally acknowledged that the carotid body (CB) type I cell mitochondria are unique, being inhibited by relatively small falls in PaO2 well above those known to inhibit electron transport in other cell types. This feature is suggested to allow for the CB to function as an acute O2 sensor, being stimulated and activating systemic protective reflexes before the metabolism of other cells becomes compromised. What is less clear is precisely how a fall in mitochondrial activity links to type I cell depolarisation, a process that is required for initiation of the chemotransduction cascade and post-synaptic action potential generation. Multiple mitochondrial/metabolic signalling mechanisms have been proposed including local generation of mitochondrial reactive oxygen species (mitoROS), a change in mitochondrial/cellular redox status, a fall in MgATP and an increase in lactate. Although each mechanism is based on compelling experimental evidence, they are all not without question. The current review aims to explore the importance of each of these signalling pathways in mediating the overall CB response to hypoxia. We suggest that there is unlikely to be a single mechanism, but instead multiple mitochondrial related signalling pathways are recruited at different PaO2s during hypoxia. Furthermore, it still remains to be determined if mitochondrial signalling acts independently or in partnership with extra-mitochondrial O2-sensors.